Analisis Tata Kelola Pusat Data dan Informasi Kementerian XYZ Menggunakan COBIT 2019 - Thio Meiza Ardi Prasetyo; Melkior N.N. Sitokdana (Journal of Applied Computer Science and Technology, 2021)
The Ministry of XYZ's Data and Information Center is a supporting element that is under and responsible to the Minister through the Secretary General with the task of preparing governance and information technology management infrastructure, developing, and implementing information system innovations and data management and information presentation. Information technology management is carried out to facilitate the management, monitoring and evaluation of every business process and information technology to achieve organizational goals. COBIT 2019 is used to assist organizations in managing and optimizing existing information technology by examining the 10 existing design factors and then analyzing the level of capability in each of the top three domains. The result of this research is the capability level of the domains BAI02, BAI03, and BAI07, which is then made recommendations from the domains that have gaps.